2019
DOI: 10.5858/arpa.2018-0032-oa
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Injury and Dendritic Cell Activation Are Integral Components of Light Chain–Associated Acute Tubulointerstitial Nephritis

Abstract: Context.— Light chain–associated acute tubulointerstitial nephritis (LC-ATIN) is a variant of light chain proximal tubulopathy (LCPT). It is characterized by interstitial inflammation with tubulitis and deposition of monoclonal light chains in the tubulointerstitium. LC-ATIN is a rather poorly recognized pattern of LCPT and not much is known about this entity. Objective.— To determine the clinicopathologic features of patients with LC-ATIN and investigate the proximal tubular injury and mechanism of interstiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We found one case with single crystals associated with lambda-LC, which is also very rarely reported in literature ( 11 ). None of the cases included in our cohort, after thorough search, met the criteria of the acute tubulointerstitial nephritis variant of LCPT, as defined previously ( 9 , 34 ). This goes in line with a cohort of LCPT published by Stokes et al ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found one case with single crystals associated with lambda-LC, which is also very rarely reported in literature ( 11 ). None of the cases included in our cohort, after thorough search, met the criteria of the acute tubulointerstitial nephritis variant of LCPT, as defined previously ( 9 , 34 ). This goes in line with a cohort of LCPT published by Stokes et al ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed increased infiltration of DCs, especially activated DCs and conventional DCs, indicating a role for these cells in the tubulointerstitial pathogenesis of DKD. Previous studies have reported that DCs were identified morphologically within the tubulointerstitium and might be involved in the pathogenesis of interstitial inflammation in drug-induced acute interstitial nephritis [ 34 ] and light chain-associated tubulointerstitial nephritis [ 35 ] . The specific mechanism requires additional experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…LCPT is an excessive accumulation of free light chains in proximal tubule epithelial cells that causes reabsorption dysfunction, tubular injury, and inflammatory reactions (Herrera, 2014; Bridoux et al, 2015; Stokes et al, 2016; Cheng et al, 2019). As reasonably conjectured, lysosomal precipitation of the monoclonal light chain is considered pathognomonic or sometimes the only pathological finding in LCPT (Larsen et al, 2011; Herrera, 2014; Stokes et al, 2016; Sethi et al, 2018; Leung et al, 2019).…”
Section: Introductionmentioning
confidence: 99%